(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Stylistic synonyms play a crucial role in enriching language, enhancing expressiveness, and allowing speakers and writers to convey subtle shades of meaning. This study investigates stylistic synonyms in English and Uzbek, highlighting their structural, semantic, and functional properties. By analyzing literary, journalistic, and everyday language examples, the research demonstrates how stylistic synonymy contributes to artistic expression, rhetorical effect, and communicative precision in both languages. The comparative approach reveals both similarities and differences in synonym usage, reflecting cultural, historical, and linguistic particularities of the two languages. The findings underscore the importance of understanding stylistic synonymy for translation, literary analysis, and language teaching.